Bibliometric Analysis with the Vosviewer-Based Keyword "Mathematical Abilities" - Muhammad Adrian; Muntazimah Muntazimah (Proceedings Series on Social Sciences & Humanities, 2023)
Using VOSviewer can help students identify current journals or articles and spot gaps in current journals. This study also aims to identify mathematical articles that get the highest number of journals, make journal rankings, determine the country where they are published and make maps to find positions in international scientific journals and. using the Google Scholar database. This study used bibliometric analysis method. The population that was the subject of this study was 1000 articles found through data analysis using the Publish or Perish (PoP) tool between 2017 and 2022. The data is recorded in Microsoft Excel as input for data processing and storage in the RIS system. use the VOSviewer app to create visuals for popular publications. There was a significant increase in articles from 2017 to reach the highest number in 2019. In graph analysis using VOSviewer software, there are two topics related to bibliometric analysis, namely "Mathematics" and "Ability" that have not been studied. a lot of things and research. . new. These topics offer opportunities for further research.